Dampak Pengaruh Artificial Intelligence terhadap Orisinalitas Karya Ilustrator Menggunakan Support Vector Machine - NST, Silvan; Akbar, Yuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study is a case study that investigates how the application of Artificial Intelligence (AI) affects the creative capacity of illustrators in the process of creating visual characters. The research focuses on the use of Stable Diffusion, a machine learning model that utilizes diffusion techniques to generate images, and the Support Vector Machine (SVM) algorithm as a method for classifying and analyzing data. By observing the interaction between illustrators and AI systems, this study aims to assess the extent to which AI influences visual style, creation methods, and the originality of resulting works. Data were collected through interviews, direct observation of the creative process, and comparisons between manually created works and those involving AI. The results indicate that AI holds significant potential to accelerate the design process and expand visual exploration, though it also presents challenges related to authenticity, dependency, and shifts in the illustrator’s role within the creative industry. SVM is used to categorize creators' perspectives on AI based on various parameters, which are then analyzed to identify common patterns. This research is expected to provide valuable insights for creative industry practitioners and academics in utilizing technology wisely without compromising artistic values and originality in illustrative works.